Jet Physics of Accreting Super-Massive Black Holes in the Era of the Fermi Gamma-ray Space Telescope - D'Ammando, Filippo (Frontiers in Astronomy and Space Sciences, 2017)
The Fermi Gamma-ray Space Telescope with its main instrument on-board, the Large Area Telescope (LAT), opened a new era in the study of high-energy emission from Active Galactic Nuclei (AGN). When combined with contemporaneous ground- and space-based observations, Fermi-LAT achieves its full capability to characterize the jet structure and the emission mechanisms at work in radio-loud AGN with different black hole mass and accretion rate, from flat spectrum radio quasars to narrow-line Seyfert 1 (NLSy1) galaxies. Here, I discuss important findings regarding the blazar population included in the third LAT catalog of AGN and the gamma-ray emitting NLSy1. Moreover, the detection of blazars at redshift beyond three in gamma rays allows us to constrain the growth and evolution of heavy black holes over cosmic time, suggesting that the radio-loud phase may be important for a fast black hole growth in the early Universe. Finally, results on extragalactic objects from the third catalog of hard LAT sources are presented.